Grand Opera and the Decline of Ballet in the later Nineteenth Century: A Discursive Essay. (November 2015) - Sasportes, José
Abstract : Up to the end of the nineteenth century, the history of ballet and the history of opera were closely entwined in a war for supremacy, with opera often in the dominant role; this was particularly the case during the second half of the nineteenth century, when ballet was widely perceived as being in decline. Some historical background is necessary to provide a brief outline of the long process that led to this outcome.